Area Law for Magnetic Domain Walls in Bent Cylindrical Nanowires - Altbir-Drullinsky, D (American Physical Society, 2022)
The dynamics of several systems in nature occurs under some constraints and symmetries that ensure the appearance of constants of motion. In this work, we discuss the dynamics of the magnetic domain wall (DW) under the Walker regime (i.e., when its position oscillates as a function of time) in bent cylindrical magnetic nanowires (NWs) with constant curvatures. It is shown that the DW position sweeps, in relation to the curvature center, the same area for different NW curvatures. This phenomenon appears due to an exchange-driven curvature-induced interaction. The translational DW motion is accompanied by its rotation around the NW axis, leading to a periodic curvature-independent angular momentum, from which one obtains an area s law for the DW motion. © 2022 American Physical Society.